2009
DOI: 10.1016/j.bbmt.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Minor ABO-Mismatches are Risk Factors for Acute Graft-versus-Host Disease in Hematopoietic Stem Cell Transplant Patients

Abstract: We investigated the impact of ABO and Rhesus (Rh) blood group matching on the outcome of hematopoietic stem cell transplantation (HSCT) of 154 patients matched at 10/10 HLA loci with unrelated donors. ABO and Rh, as potential risk factors, were modeled with the clinical outcome--acute and chronic graft-versus-host disease (aGVHD, cGVHD), relapse, treatment-related mortality (TRM), and overall survival (OS)--by simple, multiple, and competing risk analyses. We found that minor ABO-mismatches represent a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
2
23
2
Order By: Relevance
“…In a study of 174 patients by Bacigalupo et al [15], minor ABO mismatch was associated with a significantly higher risk of severe acute GVHD when compared with ABO-matched and major ABO-mismatched pairs. Ludajic et al [27] observed that a minor ABO-mismatch represents a significant risk factor for acute GVHD (grade II–IV) with an estimated risk increase of almost 3-fold, and even 4-fold for severe acute GVHD (grade III–IV). Gutiérrez-Aguirre et al [28] analyzed a cohort of patients exclusively receiving RIC and found the highest rate of acute GVHD in minor ABO-mismatched transplant recipients (25%) compared with ABO-identical (20.5%) and major ABO-mismatched cases (15.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 174 patients by Bacigalupo et al [15], minor ABO mismatch was associated with a significantly higher risk of severe acute GVHD when compared with ABO-matched and major ABO-mismatched pairs. Ludajic et al [27] observed that a minor ABO-mismatch represents a significant risk factor for acute GVHD (grade II–IV) with an estimated risk increase of almost 3-fold, and even 4-fold for severe acute GVHD (grade III–IV). Gutiérrez-Aguirre et al [28] analyzed a cohort of patients exclusively receiving RIC and found the highest rate of acute GVHD in minor ABO-mismatched transplant recipients (25%) compared with ABO-identical (20.5%) and major ABO-mismatched cases (15.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Minor ABO incompatibility has been associated with increased incidence of acute GVHD in populations who have received an allogeneic BM or PBSC transplant [34]. This increase in aGVHD is due to donor T cell sensitization against recipient ABO glycosyltransferase-derived peptides [35], which act as minor histocompatibility antigens and trigger an adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that minor and major ABO incompatibility can be associated with a higher incidence of GVHD and may also have a negative impact on outcome. [19][20][21] Endothelial replacement and chimerism by donor bone marrow-derived cells might play a role in ABO-incompatibility; theoretically it could be a result of rejection and eventually favor the development of ABO tolerance.…”
Section: Introductionmentioning
confidence: 99%